Pain-related Disability, Physical Function and Behavioural Aspects of Ankylosing Spondylitis-related Inflammatory Low Back Pain - ALRASHED ALHUMAID, LOLWAH (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2019)
Inflammatory low back pain (ILBP) is a key clinical symptom and a significant problem in ankylosing spondylitis (AS), and its high socioeconomic costs are mainly attributed to disability. Ankylosing spondylitis-related inflammatory low back pain (AS-ILBP) has been mostly managed under the biological paradigm, which generally fails to address the persistence of low back pain (LBP). This has raised the question as to whether ILBP has a multidimensional nature that must be managed using a biopsychosocial approach. To date, pain-related disability and behavioural aspects of ILBP have not been well explored, and physical function has not been objectively quantified in individuals with AS-ILBP. The aim of this thesis was to explore pain-related disability, physical function and behavioural aspects of ILBP among adults with AS-ILBP. The cross-sectional controlled Study 1 was conducted to establish a biopsychosocial LBP profile of adults with AS-ILBP. Compared to matched chronic non-specific low back pain (CNSLBP) controls, adults with AS-ILBP perceived the same levels of LBP intensity and disability. A pain-related behavioural profile was established for AS-ILBP; adults with AS-ILBP had negative pain-related cognitions, dysfunctional behaviours and psychosocial distress, and these findings were similar to those of CNSLBP controls. However, adults with AS-ILBP had significantly less fear-avoidance of physical activity (PA) and used active pain coping strategies more frequently than those with CNSLBP. Impairments in physical functional performance were present among adults with AS-ILBP, and these were nearly similar to those of CNSLBP controls. Within the AS-ILBP cohort, LBP intensity was significantly associated with most of the pain-related behavioural and perceived disease measures; but not with any of the physical function measures nor the inflammatory biomarkers. LBP-related disability was significantly associated with nearly all the biopsychosocial factors. The findings highlighted the importance to (i) systematically review the literature on the effects of behavioural interventions in AS, and (ii) to qualitatively explore the experiences of AS-ILBP. The Systematic Review (Study 2) was the first to systematically review and quantitatively synthesise controlled trials that examined the effects of behavioural interventions in adults with AS. Nine studies met the eligibility criteria. Based on two studies, the findings of the meta-analyses suggested that behavioural change interventions (BCIs) that target pain coping and PA are effective in improving physical function in the short-term. However, BCIs that only target PA are not effective in the intermediate-term for physical function, disease activity, global well-being or self-efficacy. Though, these findings should be interpreted cautiously as only two studies were included in each meta-analysis comparison. The effect of behavioural therapy on back pain intensity was only reported by a few heterogeneous studies, and their findings were conflicting. Based on individual studies, behavioural interventions based on cognitive-behavioural approach appear to have promising effects on pain, disability and physical function. The qualitative Study 3 explored the experiences of ILBP from the perspective of adults with AS. Analysis of their experiences revealed five themes relating to the ILBP: (i) experiences and perception surrounding diagnosis, (ii) perceived ILBP trajectories, (iii) impact of AS-ILBP, (iv) behavioural responses towards ILBP and (v) experience with AS-ILBP treatments. Adults with AS-ILBP experienced a delay in diagnosis, in which ILBP was negatively perceived, and dysfunctional LBP beliefs and behaviours were reported. ILBP appeared to have a multidimensional nature and impact, with the greatest impact was suggested on physical function and psychological health. While pain-related behavioural factors were viewed as both consequences and aggravators of LBP and disability, physical dysfunction was mainly viewed as a consequence of LBP. Many individuals with AS held negative ILBP beliefs that drove dysfunctional behaviours. The primary received ILBP treatment was medication and to a lesser extent physiotherapy; both described treatments had limited effects and/or side effects. The final study (Study 4) of this thesis was implemented in response to the findings and recommendations of Study 1 and Study 3. This study was the first to digitally quantify the pain extent and location of adults with AS-ILBP using a novel method of pain drawing analysis, and to compare these to adults with CNSLBP. Adults with AS-ILBP perceived significantly more widespread pain in the dorsal body area than those with CNSLBP. Widespread pain was significantly associated with negative LBP beliefs and low self-efficacy; but not with perceived physical function nor disability among adults with AS-ILBP. It is expected that the findings of this thesis will guide future research and inform clinical practice for a better assessment and management of AS-ILBP.
APPROVED
Keywords: Ankylosing spondylitis; Inflammatory low back pain; Disability; Physical function; Behavioural